Cerebellar white-matter changes in cannabis users with and without schizophrenia - Solowij, N.; Yücel, M.; Respondek, C.; Whittle, S.; Lindsay, E.; Pantelis, C.; Lubman, D. I. (Psychological medicine, 2011)
The cerebellum is rich in cannabinoid receptors and implicated in the neuropathology of schizophrenia. Long-term cannabis use is associated with functional and structural brain changes similar to those evident in schizophrenia, yet its impact on cerebellar structure has not been determined. We examined cerebellar grey and white matter in cannabis users with and without schizophrenia. Seventeen patients with schizophrenia and 31 healthy controls were recruited; 48% of the healthy group and 47% of the patients were long-term heavy cannabis users (mean 19.7 and 17.9 years near daily use respectively). Cerebellar measures were extracted from structural 3-T magnetic resonance imaging (MRI) scans using semi-automated methods, and examined using analysis of covariance (ANCOVA) and correlational analyses. Cerebellar white-matter volume was reduced in cannabis users with and without schizophrenia compared to healthy non-users, by 29.7% and 23.9% respectively, and by 17.7% in patients without cannabis use. Healthy cannabis users did not differ in white-matter volume from either of the schizophrenia groups. There were no group differences in cerebellar grey matter or total volumes. Total cerebellar volume decreased as a function of duration of cannabis use in the healthy users. Psychotic symptoms and illness duration correlated with cerebellar measures differentially between patients with and without cannabis use. Long-term heavy cannabis use in healthy individuals is associated with smaller cerebellar white-matter volume similar to that observed in schizophrenia. Reduced volumes were even more pronounced in patients with schizophrenia who use cannabis. Cannabis use may alter the course of brain maturational processes associated with schizophrenia.